Kepastian Hukum Atas Tanah Adat sebagai Objek Jaminan Hak Tanggungan dalam Surat Kuasa Membebankan Hak Tanggungan yang Dibuat Oleh Notaris/PPAT - Azrinda Rachmadanty Zahra (CV Rewang Rencang, 2025)
The accessoir agreement in the main credit agreement is an agreement related to collateral. The object of collateral can be Customary Land, as in Article 10 paragraph 3 of the Mortgage Law. The collateral is bound by the existence of a Power of Attorney to Charge Mortgage Rights or a Deed of Granting Mortgage Rights. In practice, there is still customary land that does not have a certificate. Customary land that does not have a certificate has a period of Power of Attorney to Charge Mortgage Rights for 3 months which must then be followed by the making of a Deed of Granting Mortgage Rights. If the Power of Attorney to Charge Mortgage Rights is not followed by the making of a Deed of Granting Mortgage Rights, it becomes null and void by law. Therefore, it is necessary to register customary land to be proof of perfect ownership.